ANALISIS HUBUNGAN PATRON KLIEN PADA AGRIBISNIS PADI SAWAH DI KECAMATAN BUNGA RAYA KABUPATEN SIAK - Wasiah Wasiah; Roza Yulida; Kausar Kausar (Fakultas Pertanian, Universitas Riau, 2019)
The relation of the patron clients is exchange relations between the two the role which can be expressed as a special case from the bonds of friendship that involves instrument where an individual with a higher social economy (patron) using the influence and his resources to provide a shelter, as well as the advantages for a person with a position he assumed to be lower (clients). The purpose of this reseaerch is to identify internal and external characteristic of rice farmers at bunga raya district, to identify the relation of the patron-clients in agribusiness rice fields at bunga raya district, and analyzes the relationship between characteristic of farmer to the patron client to agribusiness rice fields at bunga raya district. This research took place in Bunga Raya District of Siak Regency from March to December 2017.Survey method was used in this research with purposive as sampling technique. The results showed that the internal characteristics of farmers in Bunga Raya Subdistrict, on the age, land area and cosmopolitan variables are in the medium category, education in the low category, the number of family dependents and the length of experience in the high category. The external characteristics of farmers in Bunga Raya Subdistrict on extension intensity and accuracy of extension channels in the very high category, the number of sources of information, affordability of production input prices and the availability of inputs in the high category. Patron client relationship on the highest agribusiness subsystem is on the processing subsystem in the medium category. The relationship between patron-client on the characteristics of internal farmers is significant on the correlation that occurs between the procurement subsystem and the distribution of production facilities with the age variable and the business experience variable is a unidirectional correlation. The correlation between the primary production subsystem and the business experience variable is a weak direct correlation. Correlation between supporting subsystems with the experience variable is a weak unidirectional correlation. The correlation between processing subsystems and cosmopolitan variables is a weak direct correlation. The relationship between client patrons on external characteristics is significant in the correlation that occurs between marketing subsystems with the availability of input and is a weak direct correlation. The correlation between the procurement subsystem and the distribution of production facilities with the affordability of input production prices is a weak inverse correlation.